Balinese Purification (Melukat) Ritual: Motivation, Satisfaction, and Loyalty of Visitors - Putu Ellis Octaviyani; Made Antara; I Gusti Ayu Oka Suryawardani (Politeknik Pariwisata Bali, 2022)
Melukat ritual is a Balinese tradition which is believed to remove impurities in humans besides curing diseases. One of the main factors determining its development are motivation, satisfaction, and loyalty. The purpose of this study was to identify and analyze the influence of visitor motivation on satisfaction and loyalty. This study uses a quantitative descriptive approach to 100 respondents who have carried out the melukat ritual at Genah Melukat Sebatu, Tirta Empul Temple, Tirta Sudamala Temple and Pancoran Solas. Furthermore, the data were analyzed using the structural equation modeling (SEM) method with the smart-pls program version 3.2.2. The results showed that the push factor had a significant effect on visitor satisfaction and loyalty. Visitor satisfaction is considered capable of mediating the push factor on loyalty. The pull factor has a significant effect on visitor satisfaction; however, it has no significant effect on loyalty. Satisfaction is considered not able to mediate the pull factor on loyalty. Visitor satisfaction has a significant effect on loyalty.